Analisis Penjadwalan Pekerjaan Tanah (Land Clearing) Menggunakan Precedence Diagram Method, Pada Proyek Perumahan Bunda Asri Karangdagangan, Jombang - Andim Rendy Setiawan; Totok Yulianto; Titin Sundari; Rahma Ramadhani; Meriana Wahyu Nugroho (Pusat riset dan Inovasi Nasional, 2023)
Land work (land clearing) in the Bunda Asri housing development project was carried out to meet the contours of the land so as to reach the planned contours, according to housing project data the volume of excavation work (cut) was 374,758.15 m³ and heap (fill) was 323,320.39 m³. The volume of excavation (cut) and embankment (fill) is divided into five sections of the earthwork area with a duration of work completion of 90 calendar days. Time constraints are the reason for project or work activities to be right on plan. Scheduling in this study uses the precedence diagram method (PDM) and is assisted by Microsoft Project software. A network that has definite dependencies and can be used in projects with overlapping activities between one another's work is called PDM. The results of the research analysis used the PDM method for the construction of Bunda Asri housing, namely 81 calendar days. which is faster than the estimate of the housing developer which lasted 90 calendar days. This happened because the grouping of work with a work breakdown structure and predecessors reduced the duration time and did not precede each other among other works.